Evaluating the Productivity Using Malmquist Index Based on Double Frontiers Data. (12th September 2016) - Alimohammadlou, Moslem; Mohammadi, Sahar
Abstract: The cement industry, as a basic industry, has an essential function in the development of a country's infrastructure. This industry in Iran, however, despite numerous advantages such as high-quality mines and the use of energy at an affordable price, faces many challenges. Problems such as misuse of the production capacity in the industry threaten productivity, making it an urgent need to conduct research into this area. Generally speaking, the Malmquist productivity index can help to compare a variety of companies in the industry and to formulate a benchmark to help companies progress in this area. This research used the Malmquist index based on double frontiers data in order to provide in-depth information about the productivity of 20 companies in the Iranian cement industry. Results showed that a concomitant consideration of double frontiers, or in other words a consideration of both optimistic and pessimistic views, yielded more accurate data than those of the traditional Malmquist index, which took into account only optimistic views in calculations.